(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article investigates the pedagogical value of case study, brainstorming, and debate methods as integral strategies for enhancing creative thinking in modern education. While creativity has long been acknowledged as a critical skill in innovation-driven economies, there is still a lack of consensus on how best to cultivate it in formal learning environments. The study draws on international research and local classroom practices to evaluate how these methods encourage learners to generate original ideas, engage in reflective problem-solving, and articulate complex arguments. It demonstrates that case studies simulate real-world complexity, brainstorming encourages divergent thinking in a non-judgmental space, and debates sharpen critical and inventive reasoning through structured confrontation of ideas. Findings indicate that these methods not only stimulate creativity but also improve collaboration, self-confidence, and communication skills. The article concludes with recommendations for embedding these approaches into curricula, teacher training, and assessment frameworks to align education with the demands of the 21st century.